Current Concepts for Determining the Postpalatal Seal in Complete Dentures - Behnoush Rashedi, DMD, MS, MSEd,1 and Vicki C. Petropoulos, DMD, MS2 (Journal of Prosthodontics, 2003)
In 2001, a survey of U.S. dental schools was conducted to determine the concepts and techniques used for establishing the postpalatal seal (PPS) in a predoctoral dental curriculum.